Proceedings of the Proceedings of the 3rd English Language and Literature International Conference, ELLiC, 27th April 2019, Sem 2019
DOI: 10.4108/eai.27-4-2019.2285319
|View full text |Cite
|
Sign up to set email alerts
|

Preserving The Uniqueness of English Teaching at Early Childhood Education

Abstract: The way of early childhood teachers in introducing English to their students often seems to be unique. With a limited knowledge and skill, they have to be competent English practioners. The learning outcome migh not be optimal as the parents expected. The writer has raised questions regarding what early chilhood teachers should know and the skills they need to teach English in early chilhood education. This identified need was able to be the basic consideration to help the early childhood teachers have capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Some students still have difficulties pronouncing several letters of the alphabet, such as the frequently interchangeable spelling of the letters "f" and "v." Achieving effective and understandable English pronunciation is a complex task for students studying English as a foreign language. That's why English is different from other foreign languages because there are many different aspects, especially the sound aspect (Harmanto, 2019). Non-native speakers usually have pronunciation problems, so teachers have to work hard to figure out what strategy is appropriate to teach pronunciation to students.…”
Section: Literature Review Teaching and Learning Pronunciationmentioning
confidence: 99%
“…Some students still have difficulties pronouncing several letters of the alphabet, such as the frequently interchangeable spelling of the letters "f" and "v." Achieving effective and understandable English pronunciation is a complex task for students studying English as a foreign language. That's why English is different from other foreign languages because there are many different aspects, especially the sound aspect (Harmanto, 2019). Non-native speakers usually have pronunciation problems, so teachers have to work hard to figure out what strategy is appropriate to teach pronunciation to students.…”
Section: Literature Review Teaching and Learning Pronunciationmentioning
confidence: 99%
“…The preliminary research dealing with the ECE teachers' education qualification in introducing English in Ponorogo done by Harmanto [3], it was found that as many as 58% respondents were s1 degree holder and 42% were Senior High school graduates. Looking at the data it meant that ECE teachers formally were not prepared to teach English.…”
Section: Introductionmentioning
confidence: 99%
“…Dealing with the early childhood education teacher (ECET) education qualification, it was found that as many as 58% respondents hold bachelor degree on ECE. Meanwhile 42% of them were just graduated from senior high school (Harmanto, 2019). It was very clear they were not formally prepared to teach English.…”
Section: Introductionmentioning
confidence: 99%